Medinfo 2013 : proceedings of the 14th world congress on medical and health informatics - Lehmann, Christoph U.; Ammenwerth, Elske, 1970-; Nøhr, Christian (Studies in health technology and informatics, 2013)
"This book presents the proceedings of the MEDINFO 2013 conference, held in Copenhagen, Denmark, in August 2013. The theme of the conference is 'Conducting medical informatics by converging technologies, conveying sciences and connecting people'. The book contains 188 full papers, student papers and vision papers from the conference, as well as posters, tutorials, workshops, panels and demonstrations, selected after review from the 789 submissions received. The contributions explore not only converging multidisciplinary technologies and the rigorous scientific investigations required to explain the nature of complex phenomena, but also the human-centered designs which connect people and are crucial for realizing the immense potential of information and communication technologies in healthcare. Contributions cover four major themes: representing and understanding biomedical knowledge; enhancing care, patient safety and outcome; managing care information and workflow; and enabling cost-effective healthcare"--Publisher's website.